KONSEP KESENIAN PROFETIK DAN IMPLEMENTASINYA DALAM PENDIDIKAN ISLAM - Wawan Kardiyanto (Gelar : Jurnal Seni Budaya, 2011)
The research based on the background of art creation glowing that was influenced by the art  concept for art it self (L'art pour L'art) the art concept for art show free value, aesthetic sense and  truth more. The research tried to think about the prophetic art concept that would give advantage  and clear purpose where the art has been brought, is must proportionally with action value, aesthetic  sense and truth. The religion and social figure tried to look for the answer in debating of the art  value. This was based on the regions prophetic missions that have attention to maintain action  value, aesthetic sense and truth. The regions prophetic mission is prophetic action via theology  that becomes ideology of revolusioner that always raise the movement of civilization. This is the  prophetic ethic movement, unite to the social implementation, including art. The research knew. and also understands the prophetic art practice in Islam education. Islam as rahmatan IiI alamin  that brings love, affection for universe of course care and join in maintaining truth, goodness,  development of culture via art and education. The research used literature method with Heuristic  analysis method approach, is new understanding by doing description, reflection critic and make  conclusion in agreement and opinion of prophetic art. Furthermore the research to make receipt  of prophetic art implementation theoretically in Islam education. Prophetic art in Islam education  is something that's very important as the creativity of propagation method. Islam and prophetic art  would make our environment more beautiful as in Moslem law.Key words: art, prophetic art, Islamic art, Islamic studi